2011
DOI: 10.1007/s12540-011-0802-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen permeability of glass-forming Ni-Nb-Zr-Ta crystalline membranes

Abstract: A crystalline form of a glass-forming Ni-Nb-Zr-Ta alloy was studied as a hydrogen permeation membrane working in the temperature range from 573 K to 773 K. The crystalline membrane composed of an Nb-rich phase in an Ni 10 Zr 7 matrix demonstrated a hydrogen permeation property superior to the membrane of the same chemical composition with an amorphous structure and the values of the hydrogen permeability were found to exceed those of the Pd-based membranes. However, the mechanical stability deteriorated signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The deposited TaTiNbZr multi-principal component showe wide diffraction peak with a span of about 10° at 37°, and no obvious peak was observ indicating that the deposited TiTaNbZr multi-principal component alloy film had amorphous structure. Previous studies have shown that amorphous barrier layers ha better blocking properties [13]. Furthermore, the thickness of the barrier layer has a s nificant impact on the hydrogen permeability of the material [14,16], and the three kin of TaTiNbZr barrier layers can prevent the formation of TaPd3.…”
Section: Influence Of Annealing Temperature On Microstructure Of Mult...mentioning
confidence: 99%
See 1 more Smart Citation
“…The deposited TaTiNbZr multi-principal component showe wide diffraction peak with a span of about 10° at 37°, and no obvious peak was observ indicating that the deposited TiTaNbZr multi-principal component alloy film had amorphous structure. Previous studies have shown that amorphous barrier layers ha better blocking properties [13]. Furthermore, the thickness of the barrier layer has a s nificant impact on the hydrogen permeability of the material [14,16], and the three kin of TaTiNbZr barrier layers can prevent the formation of TaPd3.…”
Section: Influence Of Annealing Temperature On Microstructure Of Mult...mentioning
confidence: 99%
“…Therefore, the development of new ultrathin films with good mechanical properties is the main goal of many researchers in this field. This goal is usually achieved by incorporating a thin Pd layer on the surface of the alloy [3][4][5][6][11][12][13][14][15]. Group V transition metals theoretically have a higher permeability to hydrogen atoms than Pd, a feature that has been experimentally demonstrated in a number of systems [4].…”
Section: Introductionmentioning
confidence: 99%